Whole-exome sequencing in the evaluation of fetal structural anomalies: a prospective cohort study. Issue 10173 (23rd February 2019) - Petrovski, Slavé; Aggarwal, Vimla; Giordano, Jessica L; Stosic, Melissa; Wou, Karen; Bier, Louise; Spiegel, Erica; Brennan, Kelly; Stong, Nicholas; Jobanputra, Vaidehi; Ren, Zhong; Zhu, Xiaolin; et al.
Summary: Background: Identification of chromosomal aneuploidies and copy number variants that are associated with fetal structural anomalies has substantial value. Although whole-exome sequencing (WES) has been applied to case series of a few selected prenatal cases, its value in routine clinical settings has not been prospectively assessed in a large unselected cohort of fetuses with structural anomalies. We therefore aimed to determine the incremental diagnostic yield (ie, the added value) of WES following uninformative results of standard investigations with karyotype testing and chromosomal microarray in an unselected cohort of sequential pregnancies showing fetal structural anomalies. Methods: In this prospective cohort study, the parents of fetuses who were found to have a structural anomaly in a prenatal ultrasound were screened for possible participation in the study. These participants were predominantly identified in or were referred to the Columbia University Carmen and John Thain Center for Prenatal Pediatrics (New York, NY, USA). Fetuses with confirmed aneuploidy or a causal pathogenic copy number variant were excluded from WES analyses. By use of WES of the fetuses and parents (parent–fetus trios), we identified genetic variants that indicated an underlying cause (diagnostic genetic variants) and genetic variants that met the criteria of bioinformatic signatures that had previously been described to be significantly enriched among diagnostic genetic variants. Findings: Between April 24, 2015, and April 19, 2017, 517 sequentially identified pregnant women found to have fetuses with a structural anomaly were screened for their eligibility for inclusion in our study. 71 (14%) couples declined testing, 87 (17%) trios were missing at least one DNA sample (from either parent or the fetus), 69 (13%) trios had a clinically relevant abnormal karyotype or chromosomal microarray finding, 51 (10%) couples did not consent to WES or withdrew consent, and five (1%) samples were not of good enough quality for analysis. DNA samples from 234 (45%) eligible trios were therefore used for analysis of the primary outcome. By use of trio sequence data, we identified diagnostic genetic variants in 24 (10%) families. Mutations with bioinformatic signatures that were indicative of pathogenicity but with insufficient evidence to be considered diagnostic were also evaluated; 46 (20%) of the 234 fetuses assessed were found to have such signatures. Interpretation: Our analysis of WES data in a prospective cohort of unselected fetuses with structural anomalies shows the value added by WES following the use of routine genetic tests. Our findings suggest that, in cases of fetal anomalies in which assessment with karyotype testing and chromosomal microarray fail to determine the underlying cause of a structural anomaly, WES can add clinically relevant information that could assist current management of a pregnancy. The unique challenges of WES-based prenatal diagnostics require analysis by a multidisciplinary team of perinatal practitioners and laboratory specialists. Funding: Institute for Genomic Medicine (Columbia University Irving Medical Center).